2016
DOI: 10.1097/ta.0000000000001228
|View full text |Cite
|
Sign up to set email alerts
|

Police transport versus ground EMS

Abstract: Prognostic/epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 16 publications
3
61
2
Order By: Relevance
“…This finding is possibly consistent with evidence that traffic accident victims in Tanzania who are transported to the ED are significantly more likely to die when transported in police vehicles than those transported by other vehicles [ 7 ]. A comparison may be made to a study conducted in the United States showing that trauma victims transported to the ED in law enforcement vehicles were no more likely to die than those transported in emergency medical service vehicles [ 23 , 24 ]. In the present study, even though more than half of the surveyed traffic police officers had previous first aid training, only one out of every 57 officers displayed a high level of knowledge about post-crash first aid.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is possibly consistent with evidence that traffic accident victims in Tanzania who are transported to the ED are significantly more likely to die when transported in police vehicles than those transported by other vehicles [ 7 ]. A comparison may be made to a study conducted in the United States showing that trauma victims transported to the ED in law enforcement vehicles were no more likely to die than those transported in emergency medical service vehicles [ 23 , 24 ]. In the present study, even though more than half of the surveyed traffic police officers had previous first aid training, only one out of every 57 officers displayed a high level of knowledge about post-crash first aid.…”
Section: Discussionmentioning
confidence: 99%
“…However, some participants experienced police transport as dangerous or painful, and one participant’s distrust of police led him to refuse this form of transport entirely. Although police transport is rare in the U.S., and nearly 90% of cases occur in just three cities (Philadelphia, Sacramento, and Detroit), this strategy may appeal to policymakers striving to improve trauma care (Wandling et al, 2016). Cities with similar policies and those considering adopting police transport to improve trauma outcomes should evaluate the racialized and psychological dimensions of these policies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Proponents of prehospital intervention argue that the advanced training of prehospital providers may save lives by allowing early treatment of potentially life-threatening conditions such as unstable airways 3 and external hemorrhage and may prevent exacerbation of injuries such as spinal cord and vertebral column injuries. 4 Supporters of prehospital transport without interventions argue that although interventions such as intubation, intravenous line placement, and fluid administration aim to stabilize injured patients in the field, their cost in increased transit time to definitive care might outweigh their benefit.…”
Section: Introductionmentioning
confidence: 99%
“…8 The two studies of this practice have found that penetrating trauma patients had equivalent outcomes when transported by police relative to EMS. 1,9,10 While the focus has been on penetrating trauma, increased use of police transport (PT) may lead to bluntly injured patients being transported by police as well. Bluntly injured patients may have multiple injuries that are difficult for non-medical providers on scene to identify, and transport without stabilization could exacerbate their injuries.…”
Section: Introductionmentioning
confidence: 99%